1999
DOI: 10.1002/(sici)1097-4636(1999)48:1<70::aid-jbm12>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Ligament graft initial fixation strength using biodegradable interference screws

Abstract: The objective of this study was to evaluate the initial fixation strength of three types of biodegradable interference screws [an Endo Fix, 7 x 25 mm polyglycolic acid, non-self-tapping (Acufex); a biodegradable interference screw, 7 x 23 mm poly-L-lactic acid, self-tapping (Arthrex); a Bioscrew, 7 x 25 mm poly-L-lactic acid, self-tapping (Linvatec)] in comparison to a titanium interference screw (Linvatec, 7 x 25 mm) in anterior cruciate ligament reconstruction using a bone-patellar tendon-bone graft. Porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 22 publications
0
28
0
2
Order By: Relevance
“…The basic challenge that an implant designed for BPTB-graft fixation has to meet in ACL reconstruction is to provide sufficient primary stability of the bone plug attachment to allow an aggressive rehabilitation protocol. In accelerated rehabilitation, resultant forces up to 200 N are likely to occur in the graft [8,22]. The two methods we tested satisfy the stability requirement, since the ultimate loads we measured were much higher than those typically applied in vivo to the reconstructed ligament during rehabilitation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The basic challenge that an implant designed for BPTB-graft fixation has to meet in ACL reconstruction is to provide sufficient primary stability of the bone plug attachment to allow an aggressive rehabilitation protocol. In accelerated rehabilitation, resultant forces up to 200 N are likely to occur in the graft [8,22]. The two methods we tested satisfy the stability requirement, since the ultimate loads we measured were much higher than those typically applied in vivo to the reconstructed ligament during rehabilitation.…”
Section: Discussionmentioning
confidence: 69%
“…Only in one case did we observe avulsion of the bone plug because the femoral posterior wall collapsed. Other authors have observed a higher incidence of the bone plug pulling out from the tunnel [22]. Since no information is available about the size (cross-sectional area and length) of the grafts used, we are not able to judge whether the observed mode of failure is attributable to the geometry of the fixation support or to a higher number of tendon fibres which strengthened the tendon portion.…”
Section: Discussionmentioning
confidence: 99%
“…Morrison (1970) reported 169 N as the ACL force during normal level walking. Noyes et al (1984) estimated that the maximum force on the graft fixation device occurs while descending stairs and is approximately 445 N. Previous studies have shown that ligament loads of this magnitude can be generated during quadriceps muscle contraction at full knee extension (Rupp et al, 1999). All of the constructs, therefore, can be considered to be secure enough for their intended use.…”
Section: Discussionmentioning
confidence: 96%
“…Noyes et al (1984) reported that the maximum force on the graft fixation device occurs while descending stairs and is estimated to be approximately 445 N. A load of 250 N was applied in our cyclic loading protocol. Previous studies have shown that ligament loads of this magnitude can be generated during quadriceps muscle contraction at full knee extension (Rupp et al, 1999). Considering that our study represents a worst case scenario, with loads applied to the graft in a direction corresponding to the axis of the tibial tunnel, the value of 250 N seemed to be a reasonable selection for the force that the graft should be able to repeatedly withstand during in vitro testing.…”
Section: Discussionmentioning
confidence: 99%